MULTI-CRITERIA DECISION MAKING TRENDS IN ECOTOURISM AND SUSTAINABLE TOURISM - Garabinović, Dušan; Papić, Miloš Ž; Kostić, Marija (Economics of Agriculture, 2021)
The goal of this paper is to provide a comprehensive overview of application of multi-criteria decision making (MCDM) methods in papers from the field of ecotourism and sustainable tourism. A search has been done of the relevant terms in titles, abstracts and keywords found in papers from 26 prominent journals from the field of tourism belonging in Web of Science (WoS) Clarivate Analytics. It has been established which MCDM methods were used and who are the most common authors of such papers. A keyword frequency analysis was also performed. It is established there are 39 papers in the field of ecotourism and sustainable tourism where MCDM methods were applied whereby all were published after the year 2000, as well as that their number is constantly increasing.